FROM MANGA LITERATURE TO LIVE-ACTION FILM/TV: MACKENYU'S CROSS-CULTURAL ODYSSEY IN GLOBAL CINEMA - Ding, Ji (BASIS (Bahasa dan Sastra Inggris), 2024)
This research examines the career of Japanese-American actor Mackenyu Arata, particularly his roles in live-action adaptations of manga and anime, to understand his influence on cross-cultural narrative integration in cinema. The study focuses on Mackenyu's portrayal of leading and important supporting characters in several high-profile adaptations, including Netflix's One Piece, where he plays Zoro, and others such as Chihayafuru, JoJo's Bizarre Adventure, Rurouni Kenshin, and Fullmetal Alchemist. Employing qualitative analysis, this paper investigates how Mackenyu strategically navigates away from the shadow of his father, legendary actor Sonny Chiba, to forge an independent identity and career. Data was collected through reviews, audience reception studies, and box office performance, and analyzed to assess thematic consistency and cultural impact across different markets. Experts in film adaptation theory, such as Linda Hutcheon, and resources like The Routledge Companion to World Cinema provided theoretical frameworks for analyzing how narratives are adapted for global audiences and the role of actors in these adaptations. The findings reveal that Mackenyu's choices are not merely artistic but are also deliberate efforts to blend Eastern and Western cinematic traditions, enhancing his appeal as a global actor. His roles often reflect a profound engagement with his bicultural heritage, challenging the notion that he is only a "second-generation star." These roles resonate with global audiences and contribute to the ongoing discourse on cultural integration in film. The study concludes that Mackenyu is a key figure in the realm of live-action adaptations, with a unique ability to transcend cultural and cinematic boundaries.